Pengaruh Pembelajaran Berbasis Permainan Online Terhadap Kecerdasan Fisik Motorik Anak Usia Dini - Andri Arif Kustiawan; Shinta Aulia Enggarwati (FITK UIN Walisongo Semarang, 2021)
Technology is developing very rapidly so that it can simplify human work, both science, information, games, buying and selling, and so on on the internet. Apart from having an impact on the fast and easy access to information, it also has an impact on health, social, intelligence, psychological, financial and other aspects. It is excessive if it is overused to make it addictive. Such as addiction to online games, TikTok, and youtube which results in dependence and underestimates health and time. This research uses literacy studies. The purpose of this study is to present findings of the impact of gadget use on children. The results show that technological advances have both positive and negative impacts. There are various kinds of game applications that are easily accessed by children, both game content and those that can stimulate children's development, such as creativity, memory, physical motor, cognitive and so on. So it is necessary to take preventive steps so that technological developments can also reduce the negative impact on children's development.